Synthesis, Docking and Pharmacological Evaluation of Novel Homo- and Hetero-Bis 3-Piperazinylpropylindole Derivatives at Sert and 5-Ht1a Receptor - Reyes-Parada, M (2013)
A series of 3-(3-(4-(3-(1H-indol-3-yl)propyl)piperazin-1-yl)propyl)-1H- indole derivatives (3a-d and 5a-f) as homo- and hetero-bis-ligands, were synthesized and evaluated for in vitro affinity at the serotonin transporter (SERT) and the 5-HT1A receptor. Compounds 5b and 5f showed nanomolar affinities for both targets. The experimental data were rationalized according to results obtained from docking experiments. These findings are in agreement with our proposal that bis-indole derivatives can bind both targets, and might serve as leads in the quest of ligands endowed with a dual mechanism of action. © 2013 Elsevier Ltd. All rights reserved.